DESIGNING AN IMAGE CRYPTOGRAPHY SYSTEM USING THEIMAGE ELEMENTS AS CIPHERING KEYS - Saffo, Dunia (Iraqi Journal of Science, 2024)
A design and implementation of images' cryptography system is evaluated in thispaper. This system depends on the idea of allocating a part of a digital image(possibly the first block of the image) so as to produce the cipher keys for the otherparts. Circles generating algorithm is used to produce keys from the chosen block,then corresponding circles in other blocks will be encrypted using the located keys.So in this method encryption keys are brought from the plain-image (source image)it self using graphics shapes pixels.